Saúde na educação física escolar : ambivalência e prática pedagógica - Oliveira, Victor José Machado de (2014)
This study is part of inter-institutional research between UFES, USP and UFRGS that discusses training policies aimed to train and inform Physical Education (PE) students to act in the Sistema Único de Saúde (the Brazilian Unified Health System), also known as SUS. From this research our focus was on another aspect: school health. The general goal of the study was to investigate how the topic of health has been addressed in the pedagogical practices of PE in Vitória/ES, as well as in official government documents and theoretical materials of the area, realizing the possibilities of expansion and operationalization of this concept and how it might contribute to the thinking of educational initiatives for health classes in this discipline. The proposal of the intellectual work followed the efforts of appropriation and reflection in the health debate in the academic field of PE and Public Health. Still, the sociological approach of Zygmunt Bauman to the effort of reflection on the concepts of health and education was privileged, beginning with the concept of ambivalence. First, in the methodological course, we perform a mapping of documents referring to Programa Saúde na Escola (Brazilian School Health Program), known as the PSE, to the action plans of the schools in Vitoria/ES and to an interview with the coordinator of the PSE Education Secretariat of that municipality. In these documents, PE relates to the PSE from the promotion of bodily/physical activity practice component. We observe that comparing to the action plans, that discipline participates little – and when it does, is linked mostly to projects of school sports. Through this conjuncture we offered the network of public education of Vitoria/ES a continued formation for PE teachers. In this stage, we avail ourselves of the principles of action research as an investigative tool. The data was produced by diary of the continued formation, audio transcription of continued formation, analysis of documents produced by teachers in continued formation (testimonials and projects), diary accompanying in locus of the interventions in schools, emails, semi structured interviews, and participative observation. With regard to continuing education, we believe that it constituted a meaningful space for the development of a reflective, collaborative and self-managed group. The voluntary continued formation had 18 inscriptions, but only six teachers remained until the completion of work. These six built projects for health education. In the context of pedagogical innovation, it’s remarkable from the projects developed the displacement of a restricted perspective (biological) for an expanded concept of health. In this sense, the project has had an emphasis on social relationships, i.e. the aspects of care for oneself and for others, respect, inclusion and promoting the culture of peace. Another expansion of vision is embodied in the idea that health is a pedagogical issue. About the practical development of the projects, the analysis showed that these are influenced by elements relative to the school culture, violence, time and struggles for recognition. It was perceived that the projects become producers of ambivalence in school spaces, since these have caused by a series of estrangements due to not being linked to traditional social imaginary assigned to PE. The experiences developed show that health as a transversal theme must be understood as a responsibility of the whole school and not solely that discipline. Finally, education for health has proved to be a useful concept in health promotion in school spaces, which corroborates the vision and proposal of the PSE.